Biotechnological applications of microalgae : biodiesel and value added products - Bux, F. (Faizel) (Boca Raton : CRC Press, 2013)
'The book gives an in-depth analysis of microalgal biology, ecology, biotechnology and biofuel production capacity as well as a thorough discussion on the value added products that can be generated from diverse microalgae. It summarizes the state of the art in microalgal biotechnology research, from microalgal strain selection, microbiology, cultivation, harvesting, and processing. Contributors from the US, Africa, Asia, South America, and Europe cover microalgal physiology, biochemistry, ecology, molecular biology, and more'--
'Preface Over the decades, much of the literature has focused on the biology and ecological aspects of algae found in freshwater, marine, and brackish environments. These organisms are also known to inhabit various other environments on Earth. More recently, there has been a substantial shift toward the concept of sustainable development and the'green economy' with emphasis on exploiting biological systems for the benefit of mankind. This underpins the fundamentals of the field of biotechnology, which has revolutionized various fields including agriculture, food, pharmaceutical and medical sciences, environmental sciences, and industrial feedstock, thus positively impacting most spheres of human endeavor. Algae--but more specifically, microalgae--have been associated with problematic events such as algal blooms caused by eutrophication of aquatic environments and in some cases the toxins produced have serious health impacts on the aquatic environment, plants, animals, and humans. However, these events are largely due to human activities resulting in the proliferation of nutrients in aquatic environments. The significance of algae cannot be underestimated as they contribute to approximately 40% of the oxygen in the atmosphere, are the original source of fossil fuels, and are the primary producers in the oceans. Therefore, there is potential for exploitation of this invaluable biomass source that could lead to definite environmental and economic benefits for man'--
ch. 1. Introduction / Taurai Mutanda -- ch. 2. The biology of microalgae / Ranganathan Rajkumar and Zahira Yaakob -- ch. 3. Strain selection for biodiesel production / Subburamu Karthikeyan -- ch. 4. Enumeration of microalgal cells / Taurai Mutanda and Faizal Bux -- ch. 5. Microalgal cultivation reactor systems / Melinda J. Griffiths -- ch. 6. Harvesting of microalgal biomass / Manjinder Singh, Rekha Shukla, and Keshav Das -- ch. 7. Lipid identification and extraction techniques / Desikan Ramesh -- ch. 8. Synthesis of biodiesel/bio-oil from microalgae / Bhaskar Singh, Yun Liu, and Yogesh C. Sharma -- ch. 9. Analysis of microalgal biorefineries for bioenergy from an environmental and economic perspective focus on algal biodiesel / Susan T.L. Harrison, Christine Richardson, and Melinda J. Griffiths -- ch. 10. Value-added products from microalgae / Terisha Naidoo, Nodumo Zulu, Dheepak Maharajh, and Rajesh Lalloo -- ch. 11. Algae-mediated carbon dioxide sequestration for climate change mitigation and conversion to value-added products / Ajam Y. Shekh, Kannan Krishnamurthi, Raju R. Yadav, Sivanesan S. Devi, Tapan Chakrabarti, Sandeep N. Mudliar, Vikas S. Chauhan, Ravi Sarada, and Sanniyasi Elumalai -- ch. 12. Phycoremediation by high-rate algal ponds (HRAPs) / Ismail Rawat, Ramanathan Ranjith Kumar, and Faizal Bux -- ch. 13. Microalgal biotechnology : today's (green) gold rush / Ravi V. Durvasula, Durvasula V. Subba Rao, and Vadrevu S. Rao.
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: Microalgae -- Biotechnology; Biomass energy; Microalgae -- Industrial use